The potential of nanomaterials for improving tire rolling resistance - Mohd Nizar, Muhd Razali; Ahmad Noor Syukri, Zainal Abidin; Mohamad Rusydi, Mohamad Yasin; Amirul Hakim, Sufian; Nurul Nadia, Nor Hamran (Springer, 2024)
Tire design and manufacturing have undergone substantial transformations, with innovations spanning from the incorporation of nanomaterials to advanced spoke design techniques. Despite these advancements, critical gaps remain in our understanding of tire-pavement interactions, particularly under varied conditions and with different tire materials. Existing research offers crucial insights into traction influences, predominantly for off-road scenarios, but the dynamics of diverse pavement interactions warrant deeper exploration. Further challenges include achieving consistent nanomaterial dispersion within the tire’s rubber matrix and evaluating potential environmental and health impacts of these materials. Future research directions should prioritize a holistic approach that accounts for both tire and pavement characteristics, aiming to improve noise reduction, performance, and safety. Additionally, an eco-centric lens should guide the synthesis and application of nanomaterials in tire manufacturing, ensuring sustainability alongside innovation. Addressing these focal areas can pave the way for optimized, safe, and environmentally responsible tire solutions.